Exploring the management of type 2 diabetes in the Caribbean - Nixon, Amy L. (2021)
Introduction Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with a prevalence that has been increasing steadily and rapidly across the world, including the Caribbean region. It has negatively impacted individuals health and wellbeing, and in addition, it has increased the economic and social burden on the countries. T2DM management is an integral part of positive health outcomes, however, it has been poor in the Caribbean and is resulting in an alarming number of complications. The best way to reduce the negative outcomes associated with T2DM is to ensure that the disease is managed correctly. To do this, issues associated with poor T2DM management must be identified and disseminated to the public.